THE EFFECT OF KESAMBI BARK EXTRACT ON MICE LYMPHOCYTE COUNT AND SPLEEN INDEX - Christine Stefani Tamelan; Kukuh Madyaningrana; Vinsa Cantya Prakasita (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
Kesambi is a plant widely used by people of Timor Island. Flavonoid content of Kesambi is potential to be used as immunomodulators. This study aimedÂ  to study the effect of Kesambi bark extract on lymphocyte count and spleen index of male mice as an indicator of their immune responses. Research included identification of phytochemical compounds macerated from Kesambi bark, lymphocytes count and spleen index calculation. Mice injected with sheep erythrocytes were treated orally with three doses of Kesambi extract (0.113 mg/g BW, 0.491 mg/g BW, and 0.712 mg/g BW) for 10 days. Lymphocyte count using blood smear method was carried out on day 0, 5 and 10, while lymphocyte count using hematology analyzer and spleen index measurement were performed after mice sacrificed. Kesambi bark contains alkaloids, flavonoids, tannins, and steroids. Treatment with Kesambi bark extract reduced mice lymphocyte count. Administration of 0.491 mg/gr BW dose reduced the mice lymphocytes count close to the number of lymphocytes in the negative control group. The spleen index of mice had no correlation with changes in the number of lymphocytes. This preliminary study shows a potential use of Kesambi bark extract as a natural immunosuppressant.